Self-Efficacy and Parents' Perspectives of Elementary School Students in Online Learning During Covid-19 - Fitriyani, Yani; Yuliyanto, Aan; Hermawati, Eli; Darkam, Dede; Sofiasyari, Irma; Yulianto, Ade (Universitas Pahlawan Tuanku Tambusai, 2022)
This study intends to investigate the self-efficacy and perspectives of primary school parents in an online learning during COVID-19. The survey method was applied in this study with a random sampling technique for parents in West Java. Participants included in this study were 95 parents of elementary school students. The instruments applied were open and closed questionnaires. Overall, parental self-efficacy was moderate, namely 45.98. Parents' self-efficacy in public primary schools was higher than from private primary schools. However, in inferential, there was no significant difference between the self-efficacy of parents in public and private primary schools. 55% of parents rated online learning as effective. For students, 44% of parents felt that students had difficulties understanding online learning materials at home. On the other hand, 82% of parents felt student assessments assisted in learning from home. 93% of parents found it easy to access online learning. 68% of parents were satisfied with online learning during COVID-19. Thus, online learning is a breakthrough in learning activities with the use of future technology during COVID-19. Educators are also required to create interactive learning through online learning platform and with the cooperation from parents at home.